2022
DOI: 10.3389/fnhum.2022.938708
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric near-infrared spectroscopy brain-computer interface based on the detection of emotional valence

Abstract: Brain-computer interfaces (BCIs) are being investigated as an access pathway to communication for individuals with physical disabilities, as the technology obviates the need for voluntary motor control. However, to date, minimal research has investigated the use of BCIs for children. Traditional BCI communication paradigms may be suboptimal given that children with physical disabilities may face delays in cognitive development and acquisition of literacy skills. Instead, in this study we explored emotional sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…It offers advantages such as noninvasiveness, compactness, portability, and low energy consumption. Researchers have investigated hemodynamic responses associated with emotion processing in the prefrontal cortex region [7][8][9][10]. These studies demonstrated the potential for distinguishing emotional states based on hemodynamic changes and proposed emotion prediction models using machine learning techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers advantages such as noninvasiveness, compactness, portability, and low energy consumption. Researchers have investigated hemodynamic responses associated with emotion processing in the prefrontal cortex region [7][8][9][10]. These studies demonstrated the potential for distinguishing emotional states based on hemodynamic changes and proposed emotion prediction models using machine learning techniques.…”
Section: Related Workmentioning
confidence: 99%
“…(3) lightweight and highly integrated design to enhance user experiences; (4) ensuring highquality signals; (5) adopting a comfortable ergonomic design; (6) portable and wearable, lightweight, and flexible instruments; (7) cost reduction; (8) device complexity and reliability; (9) high resolution; (10) advanced signal processing algorithms suitable for long-term practical research.…”
Section: Research Gapmentioning
confidence: 99%